Space-time/frequency line coded OFDM : system design and practical implementation - Wu, Chaowu (2021)
In this paper, we investigate a class of new multiple-input multiple-output (MIMO) transmission schemes, dubbed space time line code (STLC), in the context of different mobility situations. We extend its original structure into space and frequency domains and propose a novel frequency line code (SFLC) for combining with orthogonal frequency division multiplexing (OFDM) in order to achieve potential diversity gains in time-varying multipath fading channels. Specifically, at the transmitter, the STLC/SFLC-OFDM scheme exploits the channel state information (CSI) to linearly encode successive modulated symbols in the time/frequency domain to achieve full diversity gain. At the receiver, it can retrieve the transmit symbols without full CSI, thanks to its special structure. We analyse the impact of time-variant channels to STLC and SFLC to show the expected performance degradation in practical channel, especially in the case of different mobile speeds. Our analysis and simulations show that the BER performance degrades with increasing correlation coefficient, which makes STLC-OFDM more robust in channels with abundant multipath spread, and SFLC-OFDM more robust in channels with high mobility speed. Meanwhile, a guideline is provided for switching when the communication environment changes. Finally, we carry out the practical implementation of STLC-OFDM and SFLC-OFDM schemes and characterize their performance with both computer simulations and an experimental testbed.